Analisis Pelaksanaan Sistem Pembelajaran Blok menggunakan Analisis SWOT pada Program Keahlian Teknik Ketenagalistrikan - Annisa Silvia Ningsih; Mukhlidi Muskhir (Jurnal Pendidikan Teknik Elektro, 2022)
This study aims to analyze the implementation of the block learning system using SWOT analysis so as to produce proposals in the form of strategies and policies in an effort to improve the implementation of the block system based on the results of the SWOT analysis. The study consisted of 4 respondents, consisting of school management in the field of curriculum and 3 teachers of Electrical Engineering. This research is a type of descriptive research with a qualitative approach using the SWOT (Strengthness, Weakness, Opportunities, Threats) analysis method. Data collection methods used are observation, interviews, and documentation. Data analysis was carried out using Miles & Huberman analysis with the help of a SWOT matrix. The strategies that can be developed after conducting a SWOT analysis are the SO (Strengthness-Opportunities) strategy, the WO (Weakness-Opportunities) strategy, the ST (Strengthness-Threats) strategy, and the WT (Weakness-Threats) strategy. The results showed that the block learning system at SMKN 2 Payakumbuh based on the results of the SWOT analysis, had great strengths and opportunities to support the success of the implementation of the next block learning system, although there were still some weaknesses and threats. ) were found. The strategy that can be done in an effort to improve the implementation of the block system based on a SWOT analysis is that schools strive for the implementation of the block system to be in accordance with the Teaching Factory (TEFa) program which is one of the development programs for schools.